1987
DOI: 10.1099/00221287-133-6-1589
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids Protect Against T-2 Mycotoxins both in vitro and in vivo

Abstract: Quercetin was able to reduce the cytotoxic effect of T-2 mycotoxin on cultured murine thymocytes. When given to mice immediately before challenge with T-2 mycotoxins, quercetin significantly reduced mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Accordingly, these fractions exhibited a DPPH IC 50 lower than 40 µg·mL −1 and total antioxidant capacity higher than 300 mg AAE·g −1 DW. Interestingly, these fractions all exhibited a strong protective action on bovine and porcine cells upon T2 or zearalenone exposure, suggesting that this effect is at least due to the relevant phenolic compounds present in these fractions, as it has been already reported [ 39 , 40 , 41 ]. Accordingly, Montibus et al [ 42 ] showed that the phenolic composition of a maritime pine extract, and particularly methylated compounds, would be essential for its antifungal and anti-mycotoxin properties.…”
Section: Discussionsupporting
confidence: 58%
“…Accordingly, these fractions exhibited a DPPH IC 50 lower than 40 µg·mL −1 and total antioxidant capacity higher than 300 mg AAE·g −1 DW. Interestingly, these fractions all exhibited a strong protective action on bovine and porcine cells upon T2 or zearalenone exposure, suggesting that this effect is at least due to the relevant phenolic compounds present in these fractions, as it has been already reported [ 39 , 40 , 41 ]. Accordingly, Montibus et al [ 42 ] showed that the phenolic composition of a maritime pine extract, and particularly methylated compounds, would be essential for its antifungal and anti-mycotoxin properties.…”
Section: Discussionsupporting
confidence: 58%
“…Similar results were obtained by other authors. An in vitro study (Markham et al, 1986) on thymocytes revealed that quercetin offered significant protection against cytotoxicity of T-2 toxin by reducing mortality. This protection was greatest when the drug was added before or at the same time as T-2 mycotoxin to the thymocyte…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin (3, 3′, 4′, 5, 7-penthydroxyflavone) is semi-lipophilic flavonol plentifully present in leafy vegetables, citrus fruits, tomatoes, berries, etc. It possesses several therapeutic effects such as antioxidant, anti-inflammatory, wound healing, antithrombotic, antitumor, antiprotozoal [124][125][126][127][128], and cytoprotective effects [129]. Among the different nanocarriers, polymeric nanoparticles may provide an effective way to encapsulate quercetin as they can improve bioavailability, therapeutic effectiveness, and in vivo stability.…”
Section: Quercetinmentioning
confidence: 99%